The Effect of Nutrition Education on Breast Milk Production in Postpartum Mothers - Asmin, Risna Yunita; Hadijah; Maghfira Idrus; Eka Setiawati (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2025)
Background: Breast milk is a very important thing in the process of growth and development of infants. There is no other type of milk that can replace breast milk (ASI), especially exclusive breastfeeding. Babies who receive exclusive breastfeeding have a higher level of health and intelligence, immunity to various diseases, and a higher level of emotional comfort because they are closer to their mothers. Objective: To determine the effect of nutritional education on breast milk production in postpartum mothers at RSKDIA Pertiwi Makassar in 2025. Method: This study uses a quasi-experimental design method with one group pre-test and post-test. The population in this study were all postpartum mothers who gave birth normally or by cesarean section. Sampling was carried out using a total sampling technique obtained 40 respondents. The collected data were then processed and analyzed using the SPSS version 24 statistical program and analyzed with the wilcoxon test. Results: The study showed that there were computerized statistical test results using the wilcoxon test, which obtained a p-value of 0.000, so it can be concluded that Ho was rejected and Ha was accepted, which means there is an influence of nutritional education on breast milk production in postpartum mothers.